Activity of Ligninolytic Enzymes during Growth and Fruiting Body Development of White Rot Fungi Omphalina sp. and Pleurotus ostreatus - HAPPY WIDIASTUTI; SUHARYANTO SUHARYANTO; AGUSTINA WULANINGTYAS; SUTAMIHARDJA SUTAMIHARDJA (HAYATI Journal of Biosciences, 2008)
The activity of ligninolytic enzymes of white rot fungi (WRF) Omphalina sp. and Pleurotus ostreatus was observed during somatic and fruiting body development in solid substrate fermentation using empty fruit bunches of oil palm (EFB). The enzyme activity was dominated by laccase both of Omphalina sp. and P. ostreatus. The laccase activity on somatic phase (mycelium growth) was higher compared to that of fruiting body formation phase. The laccase activity of Omphalina sp. was slightly higher compared to that of P. ostreatus. The peak activity of manganese peroxidase (MnP) for Omphalina sp. was observed two weeks after inoculation, while P. ostreatus had two peaks i.e. two and four weeks after inoculation period. The MnP activity of P. ostreatus was higher compared to that of Omphalina sp. Omphalina sp. growth in EFB did not secrete lignin peroxidase (LiP) in contrast to P. ostreatus. The peak of LiP activity of P. ostreatus was reached two and four weeks after inoculation. The MnP and LiP activities declined during the development of fruiting bodies while laccase increased both in Omphalina sp. and P. ostreatus. It seems that the activities of ligninolytic enzyme profile were regulated in line with developmental phase of growth both in Omphalina sp. and P. ostreatus. Key words: ligninolytic enzyme activity, Omphalina sp., Pleurotus ostreatus, empty fruit bunches of oil palm